VALIDITAS BUKU PENGANTAR TEKNOLOGI INFORMASI DI AREA SMK PP N PADANG - Agus Nurofik; Sartika Yuliana; Yeni M; Arnal Yanuardi; Nini Nini (Sekolah Tinggi Pariwisata Mataram, 2022)
Background: Validation of the book is very important so that the shortcomings of the developed book can be identified and can correct errors in its preparation both in terms of relevance, accuracy, language, and learning. The book that will be tested for validation is an Introduction to Information Technology in the area of SMK PP N Padang. This study aims to describe the validity of the results of the development of the book Introduction to Information Technology in the area of SMK PP N Padang as a supporting material for information technology knowledge. Methods: The type of research and development used is the Borg and Gall model (1983) which consists of 7 stages: (1) Research and information gathering, (2) Planning, (3) Initial product development, (4) Initial field trials, (5) Main product revision, (6) Main field test, (7) Operational product revision. Results: The results of the development of the Introduction to Information Technology book based on its validity obtained a score of 3.65 (very valid) and the readability test obtained a score of 3.21 (very good). Conclusion: This Introduction to Information Technology is procedurally and theoretically worthy of further study and the quality of information technology developed is good.